PENINGKATAN KEMAMPUAN GURU MENGEVALUASI METODE PEMBELAJARAN PADA TAHAPAN PERANCANGAN DAN IMPLEMENTASI PEMBELAJARAN BAHASA INGGRIS - Berlin Sibarani (BAHAS, 2009)
Any language teaching method is developed with certain  philosophical assumptions on the nature of both language and language learning. These assumptions are reflected in the other two aspects of a method, namely design and technique. Therefore, once these assumptions are clearly understood,  the other two aspects will be understood more easily. The understanding of the nature of both language and language learning is changing from time to time in line with the development of researches in language and language learning. Consequently, the language teaching methods are also changing from time to time following the developing understanding of language and language learning. Encountering such a situation, an English teacher should be able to evaluate the strength and weakness of any new method, to decide which method is the most suitable and effective to teach what aspect of the language. Since a language teaching method is developed mainly based on the nature of language, and language learning, the teacher should do the evaluation of the method based on this philosophical assumption in order to obtain accurate judgment on it, and also in order to understand it thoroughly and by so doing they can implement it properly. The mastery of the philosophical assumptions of a new method is a key factor in evaluating, understanding as well as applying it properly. On the other hand, the assumption is continuously changing due to the continuous researches conducted in these fields. In order to keep competent in evaluating a language teaching method, an English teacher should keep up with the continuous development in the two field researches.   Key words: Evaluation, Methods, dan Teaching English